Water use pattern and productivity in bed planted wheat (Triticum aestivum) under varying moisture regimes in shallow water table conditions - SINGH, KARMAL; DHINDWAL, A S; DHAKA, A K; SEWHAG, MEENA; PANNU, R K (The Indian Journal of Agricultural Sciences, 2015)
Field experiment was conducted during winter (rabi) seasons of 2010-11 and 2011-12 at Chaudhary Charan Singh Haryana Agricultural University, Hisar having shallow water table (85 to135 cm) to evaluate the water use and its components in bed planted (FIRBS) wheat (Triticum aestivum L.) under three levels of moisture regimes, viz. irrigation at IW/CPE = 0.5, 0.7 and 0.9. Depletion of soil moisture (SMD) and contribution from shallow water table (GWC) increased with stage of the crop, maximum during 86 DAS to maturity period. Soil water, in the respective two crop seasons, contributed 8.63 cm and 9.27 cm under FIRBS, and 8.10 cm and 8.77 cm with conventional method of sowing towards crop ET. Total water use was 38.24 and 40.83 cm in conventional sowing which decreased to 37.43 and 36.84 cm under FIRBS in the respective two crop seasons. The water productivity of the applied irrigation water under FIRBS was higher by 25.2 and 21.5% (630 and 305 kg/ha-cm) than conventional sowing (503 and 251 kg/ha-cm) in the respective two crop seasons. The share of soil water to crop ET was highest (37.8%) with IW/CPE=0.5 and decreased to 30.8% with IW/CPE=0.9. GWC was not influenced by varying moisture regimes in the 1st crop season, but in the 2nd season it was higher under IW/CPE=0.5 and decreased with increase in moisture regimes. The total water use in the two crop seasons was highest (40.44 and 43.71 cm with irrigation at IW/CPE of 0.9 and decreased with decrease in moisture regimes. Irrigations applied at IW/CPE=0.9 resulted in significantly higher grain yields closely followed by IW/CPE=0.7. The WUE of irrigation water applied was highest (733 kg/hacm) with irrigation at IW/CPE of 0.7 in 2010-11, but in 2011-12, it was highest (378 kg/ha-cm) with lowest moisture regimes of irrigation at IW/CPE of 0.5.